Pengaruh Kegiatan Melipat Kertas (Origami) terhadap Kreativitas Anak Usia 5-6 Tahun di TK Mandiri ABCD Kecamatan Sipoholon - Marlina Berutu; Endang Junita Sinaga; Hisardo Sitorus (Jurnal Riset Rumpun Agama dan Filsafat, 2023)
Based on the problems with children's creativity at the Mandiri ABCD Kindergarten, Sipoholon District, there are still many children who cannot fold origami independently, children cannot fold paper without instructions, children easily give up when folding paper and children lack motivation to come up with ideas and thoughts. The aim of this research is to determine the effect of paper folding (origami) on the creativity of children aged 5-6 years. This research method uses descriptive quantitative research methods. The population only consisted of 108 children aged 5-6 years and a sample of 20 people was determined using a purposive sampling technique. Data was collected using a positive closed questionnaire with 18 items. From the results of the data analysis, it can be seen that folding paper (origami) has a positive and significant influence folding paper (origami) on the creativity of children aged 5-6 years: 1) Testing the analysis requirements: a) positive relationship test obtained by the value rxy = 0.546 > rtable( a=0.05,n=20) = 0.444 apparently there is a positive relationship between variable =18)= 2.101 it turns out there is a significant relationship between variable 19,45+0.88X. With the condition that Ha is accepted and H0 is rejected. From the results of the hypothesis testing research above, it shows that the value of r calculated > r table is 0.546 > 0.444 and the value of tcount > ttable is 2.763 > 2.101 so that the research hypothesis is accepted. It can be concluded that there is a positive and significant influence between Paper Folding Activities (Origami) on the Creativity of Children Aged 5-6 Years in ABCD Mandiri Kindergarten, Sipoholon District.